Bukti Sisi Buram Proses Peradilan Pidana Indonesia pada Kasus Salah Tangkap - Muchtar, Henni (Pusat Kajian Civics Fakultas Ilmu-ilmu Sosial Universitas Negeri Padang, 2009)
Basically, all policemen have the main duties to maintain social order and security, to enforce the rule, and to give the best service to all citizens (society). But, in fact, most of them did not do their duties well and, moreover, they often arrest people who did not do any guilt at all. In some cases, many people were often forced to admit the guilt that they have never done at all. This article tries to discuss the issues related to the mistake or misjudgment of the policemen in catching or arresting people. Kata Kunci: Masyarakat,Â Polisi, Hukum, Peradilan, Pidana, Kasus